Low-heat-generation high-temperature-resistant base rubber composition, mixing method and tire
Through the use of nano -enhanced composite materials and fillers in the base glue, the problem of decreased mechanical performance of base glue under high temperature conditions under high temperature conditions is solved, and the performance of low heat and high temperature resistance is achieved, and the service life of the tire is extended.
Patent Information
- Application Number
- CN202411918816.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The mechanical properties of the existing base glues decrease under high temperature conditions, improve heat generation and tear resistance decrease, resulting in easy damage to the tire shoulders, making it difficult to meet the requirements of low heat generation and high temperature performance during high-speed driving.
Through the uneven distribution of fillers and the use of nano -enhanced composite materials, improve the modular and mechanical properties of rubber composition at high temperature, reduce the deformation of rubber composition at high temperature, and then reduce lag losses.
The high-temperature resistance of the base rubber is significantly improved, the deformation and hysteresis loss of the rubber composition at high temperatures are reduced, and the service life of the tire is extended.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tire rubber manufacturing, in particular to a low-heat-generating and high-temperature-resistant base rubber composition, a mixing method and a tire. Background Art
[0002] The base rubber is the "skeleton" of the tire, providing basic structure and strength. The base rubber is located inside the tire and mainly supports and protects the internal structure. It is usually closely combined with the internal structural layers of the tire (such as the carcass layer, belt layer, etc.), providing basic structural and strength support for the tire, and playing a role in buffering and transferring stress. The quality and performance of the base rubber directly affect the overall durability and safety of the tire. High-strength and high-durability rubber materials are usually used to ensure the overall structural stability and durability of the tire.
[0003] When the tire is running at high speed, the dynamic frequency can exceed 10Hz. The periodic compression deformation requires the base rubber to have low heat generation and good fatigue resistance. The tire is running at a high temperature of 60-80℃, and the base rubber temperature can reach 80℃. The mechanical properties of the base rubber rubber composition decrease by more than 30%, the heat generation increases, and the tear resistance decreases, which makes the tire shoulder easy to be damaged. In order to reduce shoulder damage, it is necessary to improve the high temperature resistance of the base rubber.
[0004] A Chinese invention patent (publication number: CN105384975A, publication date: 2016.03.09) discloses a low heat generation, high thermal conductivity engineering giant tire base rubber composite material and its preparation method. The invention uses submicron inorganic thermal conductive fillers and carbon nanotube bundles with both thermal conductivity and mechanical reinforcement properties to play a synergistic heat conduction role. The mechanical properties of the prepared composite material meet the requirements, the heat generation is low under dynamic conditions, and the thermal conductivity is significantly improved, thereby significantly reducing the heat accumulation of the base rubber and increasing the service life of the tire. The present invention focuses on improving the high temperature resistance of the base rubber. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a low heat generation and high temperature resistant base rubber composition, which improves the modulus and mechanical properties of the rubber composition at high temperatures by using a nano-reinforced composite material through the inhomogeneous distribution of fillers, reduces the deformation of the rubber composition at high temperatures, and thus reduces hysteresis loss.
[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions: A low heat generation and high temperature resistant base rubber composition, the rubber composition is prepared by mixing the following raw materials in parts by weight: Rubber A 65-80 parts, Filler A 30-55 parts, Activator 3.5-8.5 parts, 2.0-5.0 parts of vulcanizing agent, Anti-aging agent 1.5-4.0 parts, 20-45 parts of nano-reinforced composite materials, The rubber A is natural rubber and / or synthetic isoprene rubber, and the filler A is carbon black and / or white carbon black; The nano-enhanced wear-resistant composite material is prepared by mixing the following raw materials in parts by weight: Rubber B 20-40 parts, Filler B 1.0-10 parts, 1-4 parts of organosilicon polysulfide, 0.4-2 parts of dihydrazide compound; The rubber B is selected from butadiene rubber and / or natural rubber; the total weight of the rubber A+rubber B is 100 parts by weight, and the filler B is one or more of carbon nanotubes, graphene, and nano carbon black.
[0007] Preferably, the rubber composition is prepared by mixing the following raw materials in parts by weight: Rubber A 70-78 parts, Filler A 35-45 parts, Activator 4.0-6.5 parts, 2.5-3.5 parts of vulcanizing agent, Anti-aging agent 2.0-3.5 parts, 25-40 parts of nano-reinforced composite materials, The nano-enhanced wear-resistant composite material is prepared by mixing the following raw materials in parts by weight: Rubber B 20-35 parts, Filler B 2.0-5.0 parts, 1-2.5 parts of organosilicon polysulfide, 0.5-1.5 parts of dihydrazide compound.
[0008] Preferably, the carbon black in the filler A is one or two of N375, N330, N339, N347, and N326.
[0009] Preferably, the carbon nanotubes in the filler B are in array form, the carbon black is N375, N330, N339, N347 or N326, and the graphene is 2-10 layers of graphene oxide.
[0010] Preferably, the organosilicon polysulfide is selected from one or more of γ-mercaptopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, bis(3-mercaptopropyl)tetrasulfide, bis(3-mercaptopropyl)disulfide, mercaptoethyltriethoxysilane, mercaptopropylsiloxane copolymer, methylmercaptosilane, dimercaptoethylsilane, tetra(mercaptopropyl)silane and bis(γ-triethoxysilylpropyl)sulfide.
[0011] Preferably, the activator is selected from one or more of zinc oxide, stearic acid and zinc stearate.
[0012] Preferably, the antioxidant is selected from one or more of antioxidant 4010, antioxidant 4020, antioxidant RD, 2-mercaptobenzothiazole, and antioxidant TMQ; Preferably, the vulcanizing agent is selected from one or more of sulfur, dicumyl peroxide, vulcanization accelerator NS, vulcanization accelerator CZ, and tetramethylthiuram disulfide.
[0013] Preferably, the mixed raw materials of the rubber composition further include 0.5-1.5 parts of tear-resistant resin, 0.5-2 parts of microcrystalline wax, and 0.01-0.3 parts of scorch retarder CTP.
[0014] Preferably, the tear-resistant resin is one or more of polycyclopentadiene resin, C5 modified resin and C9 modified resin.
[0015] Preferably, the preparation method of the nano-reinforced wear-resistant composite material comprises the following steps: starting an internal mixer, setting the speed to 30-45 rpm, adding natural rubber, filler and silicone polysulfide, mixing for 25-40 seconds, adding a dihydrazide compound, continuing to mix for 1-2.5 minutes, debonding, and obtaining a nano-reinforced composite material.
[0016] Furthermore, the present invention also provides a method for preparing the rubber composition, comprising the following steps: 1) Stage 1 masterbatch: start the internal mixer, set the speed to 45-55 rpm, add rubber, filler A, activator, antioxidant, tearing resin, microcrystalline wax, mix for 30-50 seconds, remove the plug and mix for 20-30 seconds, remove the plug and mix until the temperature reaches 150-165°C to discharge the rubber, and obtain masterbatch 1; 2) Second stage masterbatch: Start the internal mixer, set the speed to 25-35 rpm, add masterbatch 1 and nano-reinforced composite material, mix for 30-50 seconds, remove the plug and mix for 20-30 seconds, remove the plug and mix until the temperature reaches 135-145°C to discharge the glue, and obtain masterbatch 2; 3) Vulcanization: Start the internal mixer, set the speed to 25-35 rpm, add masterbatch 2, vulcanizer and anti-scorch agent CTP, mix for 30-50 seconds, remove the bolt and mix for 20-30 seconds, remove the bolt and mix until the temperature reaches 105-115°C to discharge the rubber, and obtain a low heat generation and high temperature resistant rubber composition.
[0017] Furthermore, the present invention also discloses a low heat build-up and high temperature resistant tire, the base rubber of the tire is prepared by vulcanizing the rubber composition.
[0018] The beneficial effects of the present invention are as follows: the present invention enables the nano-reinforced composite material to absorb a large amount of energy during the stretching process through the inhomogeneous distribution of the filler, thereby improving the anti-destruction ability and high-temperature performance of the rubber; the dihydrazide compound enhances the chemical combination of the nano-reinforced composite material and the natural rubber, and reacts with the rubber terminal aldehyde group, carboxyl group and carbonyl group, etc., to reduce the free radical terminal activity, thereby reducing heat generation. DETAILED DESCRIPTION
[0019] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The formulations of the embodiments and comparative examples are shown in Table 1.
[0021] Table 1
[0022] The formula of nano-reinforced composite materials is shown in Table 2.
[0023] Table 2
[0024] Note: 1. Natural rubber, Thailand No. 20 standard rubber; 2. Multi-walled carbon nanotubes, a product of Shandong Dazhan Nanomaterials Co., Ltd.; 3. Sebacic acid dihydrazide compound, provided by Harbin Quaker New Materials Co., Ltd.; 4. Silicone polysulfide, bis-[γ-(triethoxysilyl)propyl] tetrasulfide produced by Jiangxi Hongbai New Materials Co., Ltd.; 5. Other additives are commercially available products.
[0025] The preparation method of the nano-reinforced composite material is as follows: The internal mixer was started and the speed was set to 40 rpm. Natural rubber, filler B and silicone polysulfide were first added and mixed for 30 seconds. The dihydrazide compound was added and mixed for 1.5 minutes. The mixture was discharged to obtain a nano-reinforced composite material.
[0026] The preparation method of the embodiment is as follows: 1) First stage mixing: start the internal mixer, set the speed to 50 rpm, add natural rubber, filler A, activator, antioxidant, tear-resistant resin, microcrystalline wax, mix for 40 seconds, remove the plug and mix for 25 seconds, remove the plug and mix until the temperature reaches 160°C to discharge the rubber, and obtain masterbatch 1; 2) Second stage mixing: Start the internal mixer, set the speed to 30 rpm, add masterbatch 1 and nano-reinforced composite material, mix for 35 seconds, remove the plug and mix for 20 seconds, remove the plug and mix until the glue is discharged at 140°C to obtain masterbatch 2; 3) Vulcanization: start the internal mixer, set the speed to 25 rpm, add masterbatch 2, anti-scorch agent CTP and vulcanizing agent, mix for 35 seconds, mix for 30 seconds with the bolt raised and the bolt pressed, mix until the temperature reaches 112°C for rubber discharge, and obtain the wear-resistant and high-temperature resistant rubber composition A or B.
[0027] The preparation method of the comparative example is as follows: 1) First-stage mixing: start the internal mixer, set the speed to 50 rpm, add all materials except the anti-scorch agent CTP, the vulcanizing agent, the dihydrazide compound and the organic vulcanizing agent, mix for 40 seconds, remove the plug and mix for 25 seconds, remove the plug and mix until the temperature reaches 160°C to discharge the glue, and obtain the masterbatch 1; 2) Second stage mixing: Start the internal mixer, set the speed to 30 rpm, first add masterbatch 1, dihydrazide compound and organic vulcanizing agent, mix for 35 seconds, remove the plug and mix for 20 seconds, remove the plug and mix until the temperature reaches 140°C to discharge the glue, and obtain masterbatch 2; 3) Vulcanization: start the internal mixer and set the speed to 25 rpm. First add the masterbatch 2, anti-scorch agent CTP and vulcanizing agent, mix for 35 seconds, mix for 30 seconds with the bolt raised and the bolt pressed, mix until the temperature reaches 112°C for rubber discharge to obtain the rubber composition.
[0028] The rubber compositions obtained in the examples and comparative examples were subjected to performance tests, and the test results are shown in Table 3.
[0029] Table 3
[0030] From the above examples 1 and 2 and comparative examples 1 and 2, it can be seen that the use of nano-reinforced composite materials can significantly improve the high temperature resistance of the tread rubber composition. Under high temperature 100°C stretching, M300 is increased by 26.7% and 19.2%; E' at 60°C is increased by 21.4% and 18% respectively; and hysteresis loss tanδ (60°C) is reduced by 23.5% and 11.5% respectively. It can be seen that the base rubber composition prepared by the present invention has low heat generation and high temperature resistance.
[0031] The above is a description of the embodiments of the present invention. Through the above description of the disclosed embodiments, professionals and technicians in the field can implement or use the present invention. Various modifications to these embodiments will be apparent to professionals and technicians in the field. The general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to these embodiments shown in this article, but will conform to the widest range consistent with the principles and novelties disclosed herein.
Claims
1. A low heat build-up and high temperature resistant base rubber composition, characterized in that: The rubber composition is prepared by mixing the following raw materials in parts by weight: Rubber A 65-80 parts, Filler A 30-55 parts, Activator 3.5-8.5 parts, 2.0-5.0 parts of vulcanizing agent, Anti-aging agent 1.5-4.0 parts, 20-45 parts of nano-reinforced composite materials, The rubber A is natural rubber and / or synthetic isoprene rubber, and the filler A is carbon black and / or white carbon black; The nano-enhanced wear-resistant composite material is prepared by mixing the following raw materials in parts by weight: Rubber B 20-40 parts, Filler B 1.0-10 parts, 1-4 parts of organosilicon polysulfide, 0.4-2 parts of dihydrazide compound; The rubber B is natural rubber; the total weight of the rubber A+rubber B is 100 parts by weight, and the filler B is one or more of carbon nanotubes, graphene, and nano carbon black.
2. The rubber composition according to claim 1, characterized in that The rubber composition is prepared by mixing the following raw materials in parts by weight: Rubber A 70-78 parts, Filler A 35-45 parts, Activator 4.0-6.5 parts, 2.5-3.5 parts of vulcanizing agent, Anti-aging agent 2.0-3.5 parts, 25-40 parts of nano-reinforced composite materials, The nano-enhanced wear-resistant composite material is prepared by mixing the following raw materials in parts by weight: Rubber B 20-35 parts, Filler B 2.0-5.0 parts, 1-2.5 parts of organosilicon polysulfide, 0.5-1.5 parts of dihydrazide compound.
3. The rubber composition according to claim 1 or 2, characterized in that: The carbon black in the filler A is one or two of N375, N330, N339, N347, and N326; And / or, the carbon nanotubes in the filler B are in array form, the carbon black is N375, N330, N339, N347 or N326, and the graphene is 2-10 layers of graphene oxide.
4. The rubber composition according to claim 1 or 2, characterized in that: The organosilicon polysulfide is selected from one or more of γ-mercaptopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, bis(3-mercaptopropyl)tetrasulfide, bis(3-mercaptopropyl)disulfide, mercaptoethyltriethoxysilane, mercaptopropylsiloxane copolymer, methylmercaptosilane, dimercaptoethylsilane, tetra(mercaptopropyl)silane and bis(γ-triethoxysilylpropyl)sulfide.
5. The rubber composition according to claim 1 or 2, characterized in that: The activator is selected from one or more of zinc oxide, stearic acid, and zinc stearate; and / or, the antioxidant is selected from one or more of antioxidant 4010, antioxidant 4020, antioxidant RD, 2-mercaptobenzothiazole, and antioxidant TMQ; And / or, the vulcanizing agent is selected from one or more of sulfur, dicumyl peroxide, vulcanization accelerator NS, vulcanization accelerator CZ, and tetramethylthiuram disulfide.
6. The rubber composition according to claim 1 or 2, characterized in that: The mixed raw materials of the rubber composition also include 0.5-1.5 parts of tear-resistant resin, 0.5-2 parts of microcrystalline wax, and 0.01-0.3 parts of scorch retarder CTP.
7. The rubber composition according to claim 6, characterized in that The tear-resistant resin is one or more of polycyclopentadiene resin, C5 modified resin and C9 modified resin.
8. The rubber composition according to claim 1 or 2, characterized in that: The preparation method of the nano-enhanced wear-resistant composite material comprises the following steps: starting an internal mixer, setting the speed to 30-45 revolutions, adding natural rubber, filler and organosilicon polysulfide, mixing for 25-40 seconds, adding a dihydrazide compound, continuing mixing for 1-2.5 minutes, and removing the binder to obtain the nano-enhanced composite material.
9. The mixing method of the rubber composition according to any one of claims 1 to 8, characterized in that: The following steps are involved: 1) Stage 1 masterbatch: start the internal mixer, set the speed to 45-55 rpm, add rubber, filler A, activator, antioxidant, tearing resin, microcrystalline wax, mix for 30-50 seconds, remove the plug and mix for 20-30 seconds, remove the plug and mix until the temperature reaches 150-165°C to discharge the rubber, and obtain masterbatch 1; 2) Second stage masterbatch: Start the internal mixer, set the speed to 25-35 rpm, add masterbatch 1 and nano-reinforced composite material, mix for 30-50 seconds, remove the plug and mix for 20-30 seconds, remove the plug and mix until the temperature reaches 135-145°C to discharge the glue, and obtain masterbatch 2; 3) Vulcanization: Start the internal mixer, set the speed to 25-35 rpm, add masterbatch 2, vulcanizer and anti-scorch agent CTP, mix for 30-50 seconds, remove the bolt and mix for 20-30 seconds, remove the bolt and mix until the temperature reaches 105-115°C to discharge the rubber, and obtain a low heat generation and high temperature resistant rubber composition.
10. A low heat build-up and high temperature resistant tire, characterized in that: The base rubber of the tire is prepared by vulcanizing the rubber composition described in any one of claims 1 to 8.
Citation Information
Patent Citations
Low-heat generation and high-thermal conductivity engineering giant tire base rubber material and preparation method thereof
CN105384975A
Tread rubber composition with low heat generation and high thermal conductivity, and mixing method thereof and tire
CN113652011A
Super wear-resistant rubber composite material and preparation method thereof
CN115477792A
Low-heat-generation tread rubber composition, mixing method thereof and low-heat-generation tire
CN116178805A
Low-heat-generation, tear-resistant rubber composition for engineering tire and preparation method therefor
WO2022100629A1